Пьесы - Островский Александр Николаевич (Пушкинская библиотека, 2000)
Экземпляры: аб. (2000) / Инвентарный номер: 42444 / Цена: / Сис.шифр: 84(2Рос=Рус)1-6 / Авт.знак: О-77 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Рус)1-6